Identification of ACE2 and TMPRSS2 Gene Polymorphisms in Covid-19 Survivors with Hypertension and Diabetes Mellitus using the rhAmp PCR Method - Setijowati, Eva Diah; Suprapti, Herni; Waskito, Budi Arief; Wulandari, Retno Dwi (Fakultas Kedokteran Universitas Brawijaya, 2025)
The Covid-19 pandemic has caused significant global mortality and morbidity. Covid -19 infection is caused by the SARS-CoV-2 virus, which requires a receptor on the host cell to enter, primarily Angiotensin-Converting Enzyme 2, encoded by the ACE2 gene, and Transmembrane Serine Protease 2, encoded by the TMPRSS2 gene. Several factors can influence Covid-19 mortality and morbidity, including gender, comorbidities such as diabetes mellitus (DM), obesity, cardiovascular diseases, and genetic factors. ACE2 and TMPRSS2 polymorphisms are believed to worsen the condition of Covid-19 patients. This study aimed to identify polymorphisms in the ACE2 (rs2285666 G>C) and TMPRSS2 (rs2070788 A>G) in Covid-19 survivors with hypertension and diabetes mellitus. The total sample was 30 hypertension and diabetes mellitus patients treated at Islamic Hospital Surabaya. A total of 3 ml of blood was drawn from the median cubital vein and placed into an EDTA vacutainer. DNA extraction was performed using the High Pure PCR Template Preparation Kit (Roche). Identification of ACE2 and TMPRSS2 polymorphisms was performed using the rhAmp SNP genotyping method with the LightCycler® system (Roche 480II). Genotyping results for ACE2 showed that 55.2% of patients had the GG (wild-type) with a G allele frequency of 68.9%. Genotyping for the TMPRSS2 showed that 60% of patients had the GG (mutant-type) with a G allele frequency of 78.3%. During Covid-19 infection, neither GG genotype (ACE2) and the GG genotype (TMPRSS2) exhibited severe symptoms.